Central Corneal Thickness of Syrian Population in Relation to Different Parameters - Alloush, Noura Jamal Nasser; Suleiman, Yusuf; Jalloul, Kahtan (Journal of medical and pharmaceutical sciences, 2021)
Objectives: The aim of this study is to determine the mean Central Corneal Thickness (CCT) among a normal Syrian population and to correlate between Central Corneal Thickness and age, gender and axial length. Methods: This study was carried out at Tishreen University Hospital in Latakia. A total of 516 eyes from 258 individuals with an age range from 18 to 56 years were studied. Central Corneal Thickness was measured using corneal topography (SIRIUS). Axial length was measured using contact ultrasound A-scan (AVISO). Results: The mean CCT was 546.7±31.2 µm with a range from 456 to 643 µm. CCT was not affected by gender. CCT significantly negatively correlated with age (p=0.001). There was no statistically significant correlation between CCT and axial length (p=0.6). Conclusions: CCT varies according to race. Among a Syrian population, CCT significantly decreased with age.